2020
DOI: 10.1037/xge0000763
|View full text |Cite
|
Sign up to set email alerts
|

Does my professor think my ability can change? Students’ perceptions of their STEM professors’ mindset beliefs predict their psychological vulnerability, engagement, and performance in class.

Abstract: Two experiments and 2 field studies examine how college students’ perceptions of their science, technology, engineering, and mathematics (STEM) professors’ mindset beliefs about the fixedness or malleability of intelligence predict students’ anticipated and actual psychological experiences and performance in their STEM classes, as well as their engagement and interest in STEM more broadly. In Studies 1 (N = 252) and 2 (N = 224), faculty mindset beliefs were experimentally manipulated and students were exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
134
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(146 citation statements)
references
References 77 publications
(153 reference statements)
12
134
0
Order By: Relevance
“…While it was founded on research, it is still in it's developmental phase. The lecturer who delivered the intervention, exhibited traits of a growth Mindset, where research has reported that this may effect the intervention itself [29], where similar effects can be seen with parents [18].…”
Section: Threats To Validitymentioning
confidence: 94%
See 1 more Smart Citation
“…While it was founded on research, it is still in it's developmental phase. The lecturer who delivered the intervention, exhibited traits of a growth Mindset, where research has reported that this may effect the intervention itself [29], where similar effects can be seen with parents [18].…”
Section: Threats To Validitymentioning
confidence: 94%
“…It must be noted the both institutions were delivering the exact same course for both years, with no additional interventions or teaching methodologies applied. Also the same lecturer, lectured in both institutions to both groups of students (both years), thus considerably reducing differences associated with different lecturer delivery methods or the lecturer themselves as a contributor to any difference in performance or Mindset changes [29]. A Welch's unequal variances t-test [45] was used to examine if any statistically significant differences existed between both student cohorts using the 12 factors collected.…”
Section: Population Analysismentioning
confidence: 99%
“…However, the impact of different aspects of autonomy-supportive strategies on mindsets has not been examined. Similarly, research suggested that a performance-oriented environment (e.g., competition for grades) versus a learning-oriented environment ( Leith et al, 2014 ), generic statements (e.g., “boys are always good at math”) versus specific statements (e.g., “That student is good at math”; Cimpian, 2010 ), and ability praise (“You are so smart”) versus process praise (e.g., “Good Job, you worked so hard”; Pomerantz and Kempner, 2013 ) can strengthen fixed mindsets (see Haimovitz and Dweck, 2017 ; Muenks et al, 2020 ). Although these antecedents of mindsets may share overlap with autonomy-support strategies, they have not been systematically studied in reference to the SDT literature.…”
Section: Discussionmentioning
confidence: 99%
“…More work is needed to better understand which factors contribute to students' recovery from the initial motivational shock and to support students who are most at risk of negative motivational trajectories after the transition to higher education. Such factors might include students' mindset beliefs about the fixedness or malleability of their abilities or students' perceptions of their instructors' mindset beliefs (Dweck & Yeager, 2019;Muenks et al, 2020).…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%